Intermediate crystallization kinetics in Germanium-Tellurides. (1st February 2019) - Chen, Yimin; Pan, Hongbo; Mu, Sen; Wang, Guoxiang; Wang, Rongping; Shen, Xiang; Wang, Junqiang; Dai, Shixun; Xu, Tiefeng
Abstract: Germanium-Telluride has been widely studied as a phase-change material due to its fast crystallization speed. The understanding of the crystallization kinetics is important to evaluate the potential applications of the material, but this is limited by the conventional calorimetry with low heating rate and narrow temperature range. We here employed an ultrafast calorimetry method, named flash differential scanning calorimetry, to investigate the crystallization kinetics of Gex Te100-x in a wide compositional range (15 ≤ x ≤ 55). By means of the X-ray diffraction, we found the complicated competition between crystalline GeTe and Te (or Ge) phases in these binary alloys. The crystallization kinetics of first crystalline phase were estimated and it was found that, Gex Te100-x generally has intermediate crystal growth speed and fragility, which is ascribed to the border between covalent and metallic properties. Component dependences of maximum crystal growth rate ( U max ) and fragility were investigated, revealing the component in x = 20.4 has the lowest U max of 1.22 × 10 −3  m s −1 with the smallest fragility of 42.2, and the component in x ≈ 50 possesses the largest U max of 3.5 m s −1 . It confirms that, GeTe is the most suitable phase-change material for information storage and GeTe4 is the best media for information transparency in Ge-Te binary. Moreover, a tri-counter pattern was carried out for obtaining the crystal growth rate directly in studied supercooled Gex Te100-x liquids (15 ≤ x ≤ 55). In addition, we first found a peculiar component Ge22 Te78 with terrible thermal properties, i.e., phase separation, low crystallization temperature, ultrahigh fragility and anomalous crystallization kinetics. More importantly, together with the crystallization kinetics parameters of other glass formers, it was found a specific relation between reduced glass temperature ( T rg ) and U max for which can be benefit to simplify material screenings and performance optimizations. Graphical abstract: Image 1